Development of Physics Module Based on Ethnoscience with the Local Wisdom of House Limas Palembang to Improve Thinking Ability - Sela Melinia; Ismet; Muhamad Yusup (Postgraduate, University of Mataram, 2024)
An ethnoscience-based physics module with the local wisdom of Palembang pyramid houses to improve students' creative thinking skills in high school has been successfully developed which is valid, practical and effective. This research aims to produce ethnoscience-based physics modules with local wisdom of Palembang pyramid houses to improve students' creative thinking skills in high school. The research method used was development research with the Rowntree development model consisting of three stages: planning, development, and evaluation. The evaluation stage was conducted by adopting Tessmer's formative evaluation technique. The results showed that the ethnoscience-based physics module with the local wisdom of Palembang pyramid houses developed was categorised as very valid in the material and language components with an average percentage of 95.10% and 92.26% respectively, and categorised as valid in the presentation and display components with an average assessment percentage of 76.25%. The ethnoscience-based physics module with local wisdom is also categorised as very practical after passing the one-to-one evaluation and small group evaluation stages with an average percentage of 95.27% and 95.33% and effective in improving the creative thinking skills of students in high school with an average n-gain of 0.62 The research concluded that improving students' creative thinking skills can be done by using ethnoscience-based physics modules with local wisdom.